Social Cohesion, Religious Beliefs, and the Effect of Protestantism on Suicide - Sascha O. Becker; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2015)
In an economic theory of suicide, we model social cohesion of the religious community and religious beliefs about afterlife as two mechanisms by which Protestantism increases suicide propensity. We build a unique micro-regional dataset of 452 Prussian counties in 1816-21 and 1869-71, when religiousness was still pervasive. Exploiting the concentric dispersion of Protestantism around Wittenberg, our instrumental-variable model finds that Protestantism had a substantial positive effect on suicide. We address issues of bias from mental illness, misreporting, weather conditions, within-county heterogeneity, religious concentration, and gender composition. Tests that discriminate between the two mechanisms based on historical church-attendance data and modern suicide data suggest that the sociological channel dominates the theological channel.
Keywords: Z12; N33; 330; religion; suicide; social cohesion